Kerkbegrip en kerkorde: ’n Vergelykende studie tussen die vier Afrikaanse gereformeerde kerke in Suid-Afrika - van Wyk, Barry (Stellenbosch Theological Journal, 2021)
Church concept and church order: a comparative study between the four Afrikaans reformed churches in South Africa This article is about the church concept and church order as formulated by churches of Reformed offspring, especially since the Reformation. To be more specific: since the day when Martin Luther voiced his disgust in the church of his days in public on 10 December 1520. Church concept and church order is a Scriptural debate because both follows from a Christological ecclesiology. The second part of the article compares the church orders of the churches in South Africa with themes typically inherent to church orders of Reformed standing. This includes themes like the offices of the church, church discipline, as well as matters related to being anti-hierarchical and anti-independentistic with reference to the Reformed churches.